Acute Venous Thromboembolism Plasma and Red Blood Cell Metabolomic Profiling Reveals Potential New Early Diagnostic Biomarkers: observational clinical study - Febra, Claudia (2024)
Background: Venous thromboembolism(VTE) is a leading cause of cardiovascular mortality. The diagnosis of acute VTE is still based on complex imaging exams due to the lack of biomarkers. Moreover, studies assessing the diagnostic capacity of novel metabolomics biomarkers in VTE are scarce. Our aim was to determine whether patients with acute VTE have differences in the metabolomic profile from plasma and red blood cells (RBCs). Methods: This observational trial included 62 patients with clinical suspicion of acute deep vein thrombosis (DVT) or pulmonary embolism (PE) admitted to the emergency room (ER). After gold standard imaging exams, we analysed the plasma and RBCs from 50 acute VTE and 12 nonacute VTE patients. We performed a metabolomics study and used mixed-effects modelling to compare the differences in metabolites. Results: The plasma metabolome had a suboptimal capability for differentiating between the presence or absence of acute VTE, with 23 significantly different molecules, but with ‘good’ performance for the best ROC curves. The metabolic pathway of D-glutamine and D-glutamate had the strongest impact on the acute VTE phenotype (p = 0.001, false discovery rate = 0.06). RBCs revealed a consistent metabolomic signature of acute VTE. Among the 23 differentially abundant metabolites, we found 3 high-performance ROC curves with an area under the curve (AUC) higher than 0.9, including adenosine 3',5'-diphosphate (0.983), glutathione (0.923), and adenine (0.91). The metabolic set most impacting the differences observed was purine metabolism (p = 0.000354, false discovery rate = 0.68). Conclusions: Our findings show that metabolite differences exist between acute VTE and nonacute VTE patients admitted to the ER in the early phases. Three potential biomarkers obtained from RBCs showed high performance for acute VTE diagnosis. Further studies should investigate accessible laboratory methods for the future daily practice usefulness of these metabolites for the early diagnosis of acute VTE in the ER.